2004
DOI: 10.1081/lesb-200030880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoflavones on Reproductive Performance, Testosterone Levels, Lipid Peroxidation, and Seminal Plasma Biochemistry of Male Rabbits

Abstract: The objective of this study was to determine the effect of either 2.5 mg/kg Body Weight or 5 mg/kg Body Weight (BW) doses of isoflavones on semen quality, testosterone levels, lipid peroxidation and semen biochemistry of male New Zealand White rabbits. Animals were given both 2.5 mg/kg BW and 5 mg/kg BW doses of isoflavones. The tested doses were given to rabbits orally every other day for 13 weeks. Treatment with isoflavones caused an increase (p < 0.05) in libido (by decreasing the reaction time), sperm conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…It is advisable that further study on molecular mechanism of SI oxidation resistance could be carried out in vivo and in vitro. It had been reported that after treated with high dose SI for 12 months, morphological and histopathologic assessment of testis, sperm quality remained unchanged in rats (Faqi et al 2004), humans (Beaton 2010), rabbit (Yousef et al 2004;Cardoso 2007), mouse (Jung et al 2004), and monkey (Sharpe et al 2002). In our study, there were no changes observed in pH, volume, viability, motility and acrosome integrity in bucks with SI supplementation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It is advisable that further study on molecular mechanism of SI oxidation resistance could be carried out in vivo and in vitro. It had been reported that after treated with high dose SI for 12 months, morphological and histopathologic assessment of testis, sperm quality remained unchanged in rats (Faqi et al 2004), humans (Beaton 2010), rabbit (Yousef et al 2004;Cardoso 2007), mouse (Jung et al 2004), and monkey (Sharpe et al 2002). In our study, there were no changes observed in pH, volume, viability, motility and acrosome integrity in bucks with SI supplementation.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study we did not observe any changes in testosterone concentration as a result of SI supplementation. Other studies also reported no effects of SI on testosterone concentrations in roosters (Gjorgovska and Filev 2013) and rabbits (Yousef et al 2003;Yousef et al 2004). A seasonal variation in reproductive performance can be observed in goats, which accompanied the changes in hormone secretion.…”
Section: Discussionmentioning
confidence: 92%
“…It is suggested that endogenous estrogen state, individual variation, duration and dose of phytoestrogen affects its act as an estrogen agonist or antagonist (Cassidy, 2003). Several studies reported that ISF improved growth and reproductive performance of the animals and their products (Yousef et al, 2004;Jiang et al, 2007;Shin et al, 2008). Furthermore, Shi et al (2013) reported that feeding ISF to laying hens at 59 weeks of age showed an increase in egg production.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activities of Propolis and its polyphenolic/flavonoid components are related to their ability to chelate metal ions and scavenge singlet oxygen, superoxide anions, peroxyl radicals, hydroxyl radicals and peroxynitrite (61) . Also, Yousef et al, (62) showed that the treatment with isoflavones as antioxidant in combination with cypermethrin minimized its hazardous effects. Kanbura et al (63) found decreases in the plasma and the tissues malondialdehyde (MDA) levels and normalization in the antioxidant enzyme parameters of animals that were administered Propolis in association with propetamphos, in comparison to the group that was administered propetamphos alone.…”
Section: (33)mentioning
confidence: 99%